On Interval-valued Anti Fuzzy Prime bi-ideal of Semigroup - S. A. Wuhaib; Akram S. Mohammed; Zeyad. M. Abdullah (Tikrit Journal of Pure Science)
In this paper, we introduce the notions of interval-valued anti fuzzy prime (resp. strongly prime and semiprime) bi-ideals of semigroup. By using these ideas, we characterize those semigroup for which each interval anti-fuzzy bi-ideal is semiprime and strongly prime.